Home-based palliative approach for people with severe multiple sclerosis and their carers: study protocol for a randomized controlled trial. Issue 1 (December 2015) - Solari, Alessandra; Giordano, Andrea; Grasso, Maria; Confalonieri, Paolo; Patti, Francesco; Lugaresi, Alessandra; Palmisano, Lucia; Amadeo, Roberta; Martino, Giovanni; Ponzio, Michela; Casale, Giuseppe; Borreani, Claudia; et al.
Abstract Background Preliminary evidence suggests that palliative care may be useful for people with severe multiple sclerosis (MS). The aim of this study is to determine the effectiveness of a home-based palliative approach (HPA) for people with severe MS and their carers. Methods/design This is a single-blind randomized controlled trial with a nested qualitative study. Seventy-five severe MS-carer dyads are being randomized (at three centers, one in each area of Italy) to HPA or usual care (UC) in a 2:1 ratio. Each center has a specially trained team consisting of four professionals (physician, nurse, psychologist, social worker). The team makes a comprehensive assessment of the needs of the dyads. HPA content is then agreed on, discussed with the patient's caring physician, and delivered over six months. The intervention is not intended to replace existing services. At later visits, the team checks the HPA delivery and reviews/modifies it as necessary. HPA and UC dyads are assessed at home by a blind examiner at baseline, and three and six months later; they also receive monthly telephone interviews. Dyads assigned to UC receive the examiner's visits and telephone interviews, but not the team visits. Primary outcome measures are changes in symptoms (Palliative care Outcome Scale-Symptoms-MS, POS-S-MS), and quality of life (the Schedule for the Evaluation of Individual Quality of Life-Direct Weighting (SEIQoL-DW), not assessed in patients with severe cognitive compromise) at three and six months. Other outcomes are changes in patient functional status and mood; changes in carer quality of life, mood and caregiving burden; costs; incorporation with standard care; unplanned hospital admissions; referrals to hospice; and deaths. The experience of participants will be evaluated qualitatively by individual semi-structured interviews (HPA patients and carers) and focus group meetings (HPA patients' caring physicians). Discussion The results of our study will show whether the HPA is feasible and beneficial to people with severe MS and their carers living in the three Italian geographic areas. The nested qualitative study will add to the understanding of the strengths and limitations of the intervention. Trial registration The trial was registered with Current Controlled Trials (identifier:ISRCTN73082124 ) on 19 June 2014.